A Hunting and Fishing Legacy at Fort Riley - Alan Hynek (Symphony in the Flint Hills, 2013)
Balancing the needs of the military mission with natural resources management and the recreational interests of soldiers, families, and civilians is a challenge, but one that Fort Riley has successfully met for decades.
Keywords: elk; natural; animals; soldiers; family; recreation; military; Fort Riley; cavalry parade field; Big Red One; warriors; troops; birds; fishing; hunting; Kaw River; Camp Center; Smoky Hill River; Republican River; Rod and Gun Club; Kansas State University; Kansas Fish and Game Commission; Department of Biology; wild turkey; outdoor; Northern Bobwhite; Greater Prairie Chicken